Application Of Law And Criminal Accountability Against Violent Theft Offenders - Pratama, Erfan Putra; Susilowati, Tri (CV. Publikasi Indonesia, 2023)
The components of the wrongdoing of burglary with brutality are referenced in Article 365 of the Lawbreaker Code which should be met, for example in paragraph (1)